IJOD MAKTABLARIDA FOYDALANILAYOTGAN INGLIZ TILI DARSLIGI LASER B1 DA O‘QUVCHILARNING TANQIDIY FIKRLASH MALAKALARINI RIVOJLANTIRISH BO‘YICHA BERILGAN MASHQLAR - Ismoiljonov Shuxratjon Boymirza o‘g‘li (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2024)
This article analyzes the exercises aimed at developing students‟ critical thinking skills in the English language textbook “Laser B1”, which is used in creativity schools in our Republic. The study reveals the role and importance of critical thinking in the creative and intellectual development of students. The content of the textbook” Laser B1 student's Book " is studied in depth, in which it is assessed to what extent the exercises and tasks presented to students to form critical thinking are effective. As a result of the study, existing approaches to the development of critical thinking and practical recommendations for improving the textbook are presented.